YURIDICAL ANALYSIS SYUF`AH RIGHTS IN LAND SALE AND PURCHASE TRANSACTIONS (Case Study In Darussalam District) - Nurhisam, Luqman; Abdullah, Arifin; Fauzan, Faisal; Nurdianti, Nurdianti (Universitas Islam Negeri Ar-Raniry, 2023)
Land buying and selling transactions are closely related to people's lives which are a benchmark for whether or not the public understands land buying and selling transactions as regulated in Islamic law and Indonesian positive law. Disobedience in carrying out land sale and purchase transactions can lead to disputes which result in disputes in the future in society. Land buying and selling transactions that occur in the Darussalam sub-district community are the object of research conducted to see how the process of buying and selling land occurs whether there is an application of syuf`ah rights according to the provisions in fiqh muamalah and Islamic law. In this study, the main focus of the research is how the practice of buying and selling land in Darussalam sub-district, how is the existence of the application of syuf`ah rights that occur in society and how is the juridical analysis of syuf`ah rights in buying and selling land. The method used in this study is the method qualitative and sociological juridical with the type of field research (field research) and library research (library research). Research data were analyzed by means of descriptive analysis. Based on the analysis, it shows that land buying and selling transactions are in accordance with the applicable land sale provisions, in practice the community enforces syuf`ah activities in the process and becomes a necessity in land buying and selling transaction activities, but there are still those who do not carry them out due to a lack of understanding of syuf'ah rights . In this study, it was found that not all local people know the mention of syuf`ah rights in their daily lives, mention of syuf`ah rights in general is often referred to as